Heavy Chain Antibodies: The panacea for human health or just incomplete proteins? - Ferrari, Alejandro (2013)
Since 1993, Heavy Chain Antibodies (HCAbs) have been in the eye of a biotechnological storm. Ever since their discovery, several research groups as well as biomedical foundations and pharmaceutical companies have devoted their efforts to produce recombinant variable fragments (VHH) specific for therapeutic targets, based on HCAbs. They were supposed to be nonimmunogenic, and the smallest peptides with specific binding capacity and nanomolar affinity, and therefore expected to be an endless source of bio-drugs. In this context, a camelid-fever extended worldwide along with a sudden interest in breeding, selling and buying these animals. However, very few research groups showed interest in the health of these species, and even fewer in the immunobiological role of HCAbs in vivo. Why do these animals bear such proteins? Why has this feature only been found in camelids and cartilaginous fish? Is there any advantage in HCAbs when compared to conventional antibodies? This review is focused on the origin of the interest scientists had for HCAbs, and is aimed to understand the reasons for the generalized cooling-down of the HCAbs fever, and the sudden regained interest on camelids? health and immune system. We here review the history of HCAbs from their discovery to the current status of the knowledge about their immune system. Heavy Chain Antibodies: The panacea for human health or just incomplete proteins?